2010
DOI: 10.1038/ki.2010.334
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the treatment of vascular calcification

Abstract: Vascular calcification is common in patients with advanced chronic kidney disease and is associated with poorer outcomes. Although the pathophysiology is not completely understood, it is clear that it is a multifactorial process involving altered mineral metabolism, as well as changes in systemic and local factors that can promote or inhibit vascular calcification, and all of these are potential therapeutic targets. Current therapy is closely linked to strategies for preventing disordered bone and mineral meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 111 publications
1
55
0
1
Order By: Relevance
“…Atherosclerosis is restricted to large and medium-sized conduit arteries and has been linked mainly to "traditional" risk factors like smoking, obesity, dyslipidaemia, hypertension and aging. By contrast, media calcification can occur in arteries of any size, is a typical age-related process and has been associated with increased stiffness and reduced cushioning function [17,18]. In patients with diabetes mellitus and/or chronic kidney disease, both forms of calcification are present but are usually not distinguished in epidemiological studies, since non-ambiguous discrimination is hardly achievable unless vessel specimens for histological evaluation are available [19].…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Atherosclerosis is restricted to large and medium-sized conduit arteries and has been linked mainly to "traditional" risk factors like smoking, obesity, dyslipidaemia, hypertension and aging. By contrast, media calcification can occur in arteries of any size, is a typical age-related process and has been associated with increased stiffness and reduced cushioning function [17,18]. In patients with diabetes mellitus and/or chronic kidney disease, both forms of calcification are present but are usually not distinguished in epidemiological studies, since non-ambiguous discrimination is hardly achievable unless vessel specimens for histological evaluation are available [19].…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…[5][6][7][8][9][10] However, satisfactory therapies have not yet been established. 11 Adenine-induced renal failure is one of the commonly used animal models for studying the development of vascular calcification, but the prevalence of vascular calcification in this model is not very high. Indeed, Price et al reported that vascular calcification was detected in only 30% of rats with adenine-induced chronic renal failure (adenine rats) fed a normal-protein diet.…”
mentioning
confidence: 99%
“…The risk of inducing hypercalcemia and hyperphosphatemia with the administration of high doses of calcitriol in CKD patients led to the search for analogs that retain the effect of calcitriol on parathyroid glands while lacking the hypercalcemic and hyperphosphatemic effects [56] . New vitamin D compounds already in clinical use, which have an improved side effect profile, are limited to paricalcitol, 22-oxacalcitriol, and doxercalciferol [57] .…”
Section: Vitamin D Analogs and Vascular Calcificationmentioning
confidence: 99%
“…All the processes involved in the development of vascular calcification, mainly the systemic and local factors that can promote or inhibit vascular calcification, are potential therapeutic targets which are just being evaluated (see O'Neill and Lomashvili [56] for a recent revision).…”
Section: Vitamin D Analogs and Vascular Calcificationmentioning
confidence: 99%